Pengembangan Film Kartun Sebagai Media Pembelajaran Tematik Siswa Kelas IV SDN 9 Sampurtoba, Kec. Harian - Robenhart Tamba; Rohayati Sihotang (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is a development research (R&D) using the ADDIE development model which consists of: 1.) Analysis; 2.) Design; 3.) Development; 4.) Implementation; and 5.) Evaluation. Data collection was carried out by interviews, questionnaires and tests. The results of the interviews were analyzed descriptively qualitatively, while questionnaires and tests were analyzed quantitatively. Validation was carried out by questionnaire instrument experts, material experts, media experts and practitioner experts by class IV educators. The results of the analysis show that cartoon film learning media is included in the